Expressão do transportador de monocarboxilato MCT1 e sua proteína auxiliar CD 147 em hemácias de equinos de salto - Feringer Júnior, Walter Heinz [UNESP] (2014)
We evaluated the expression of monocarboxylate transporter 1 (MCT1) and its ancillary protein CD147 in equine erythrocytes of Brazilian (BH) and European show jumphorses.We used 29 horses , 16 of BH breed divided into two groups according to his historical show jump competitions, group underperformed (DI, n = 8) and group of superior performance (DS, n = 8) this division was confirmed by calculating the Cost of Heart Rate (CFC) and Cost of Lactate (CLAC) and 13 horses of European origin which were classified as Elite group due to the history of participation in events with greater heights than BHs. The BHs were tested twice, with a incremental speeds test (TVI) and a test of incremental jumps (IST) where values of heart rate (HR) and lactate were evaluated before and after the tests as well as blood for the Western blot, Elite animals blood were collected before and after Copa São Paulo of show jump. There was a statistical difference (p≤ 0.05) in the CFC and CLAC between DI and DS groups in IST, the same was not found for TVI. Regarding the expression of MCT1 and CD147 , significant differences (p ≤ 0.05) at baseline between the BHs and the Elite group, no differences in expression were found between DI and DS groups in any evaluation periods and the Elite group had higher expression (p ≤ 0.05) of CD147 after the show jump competition. It was concluded that BH’s expression of MCT1 and CD147 is higher when compared to European breeds and that they express more CD147 after an acute bout of effort